Kajian Teknis Perencanaan Desain Peledakan Untuk Mengurangi Getaran Tanah di PT Pamapersada Nusantara Site PT Bukit Asam Tbk: Study Of Blast Design Technical To Minimize Ground Vibration At PT Pamapersada Nusantara Site PT Bukit Asam Tbk - Pebrianto, Rosihan; Wibowo, Satriya; Al Hadi, Alex (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2025)
The impacts of drill and blast activities is ground vibration. A limit of PPV according to SNI is 5 mm/s for buildings with foundations, masonry and cement. The average PPV in this blasting activity is 2 mm/s. The community is complain that level of ground vibration produced was still felt and worried damage the building. So, PT Bukit Asam Tbk has made a regulation of the ground vibration is ≤ 1 mm/s for blasting in the near houses. The purpose of this study is to make a blast design geometry form burden, spacing, and stemming, weight of explosives maximum, , delay configuration, and estimate of the fragmentation in 800m by PPV ≤ 1 mm/s. This research method uses quantitative research methods by observing, collecting and processing data, testing data results, and making blast designs. The results show that the PPV value can be predicted using the equation of non-linear power regression. The design of the blasting geometry to obtain a PPV value of ≤ 1 mm/s is by using a presplit method, with a vulnerable space of 6 – 7.5 m, a burden of 5 – 6.5 m, and a maximum of explosives is 24-40 Kg/hole.